Assessing the Relationships Between Past Victimization, Perceived Risk of Future Victimization, and Controversial Criminal Justice Policies Using Structural Equation Modeling - Dolliver, Matthew J. (Criminal justice policy review, 2022)
Several decades of research show a strong relationship between past victimization and perceived risk of future victimization. Yet, few studies have explored the potential connection to individuals’ support for criminal justice policies. The purpose of this study is to better understand the relationships between past victimization, perception of risk for future victimization, and support for several criminal justice policies (e.g., stand your ground, open carry, three strikes, and the death penalty). Through structural equation modeling, the researchers examined relationships between these latent variables. Having both a history of victimization and a belief in the risk of future victimization increased one’s support for punitive and self-protective policies. Implications for future research and potential policies and services for victims/survivors are discussed.